Faktor-Faktor Yang Berhubungan Dengan Penerapan Model Praktik Keperawatan Profesional - Lestari Harefa; Raden Rumiris Pardede (Jurnal Keperawatan Florence Nightingale, 2026)
The Model of Professional Nursing Practice (MPNP) is a nursing care system that emphasizes professionalism in the delivery of nursing care to improve service quality, nurse performance, and patient satisfaction. Optimal implementation of the MPNP is crucial to ensuring the quality of continuous nursing care. However, based on results of a preliminary study at Hospital X, there are still nurses who have not optimally implemented the MPKP. Knowledge and length of service are factors suspected to be associated with the implementation of the MPKP. This study aims to determine the relationship between knowledge and length of service and the implementation of the Professional Nursing Practice Model. This study used a quantitative research design with a cross-sectional approach. The population consisted of all practicing nurses at Hospital X. The study sample comprised 91 respondents selected using accidental sampling. Data collection was conducted using a knowledge questionnaire and a questionnaire on the implementation of the MPKP. Data analysis was performed using univariate and bivariate analyses with the Chi-Square test at a significance level of p < 0.05. Total of 37 respondents (43%) had poor knowledge, while the majority of respondents had long tenure, namely 51 people (59.3%). A total of 29 respondents (33.7%) demonstrated ineffective implementation of MPKP. Statistical analysis showed no significant relationship between knowledge and the implementation of MPKP (p-value = 0.254) or between length of service and the implementation of MPKP (p-value = 0.578). Knowledge and length of service are not significantly associated with the implementation of MPKP.